2019
DOI: 10.1002/marc.201900322
|View full text |Cite
|
Sign up to set email alerts
|

Backbone Structure Effect on the Thermoelectric Properties of IDT‐Based p‐Type Conjugated Polymers

Abstract: Four conjugated polymers are synthesized through indacenodithiohene (IDT) unit copolymerized with thiophene and thiophene derivatives. Indacenodithiohene‐co‐thieno[3,2‐b]thiophene (IDT‐TT) and indacenodithiohene‐co‐trans‐1,2‐di(2‐thienyl)ethylene (IDT‐TVT) exhibit better charge transport mobilities than indacenodithiohene‐co‐thiophene (IDT‐T) and indacenodithiohene‐co‐3,4‐ethoxylene dioxythiophene (IDT‐EDOT), and also display superior thermoelectric properties after doping. Theoretical calculations suggest tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…[ 8–10 ] Commonly used conductive polymers are usually based on a conjugated backbone structure, like in polyacetylene, polypyrrole, polyaniline, or polythiophene. [ 11 ] With different techniques of doping, [ 12–14 ] side chain variations, [ 14 ] or backbone modifications [ 15 ] the thermoelectric performance can be positively influenced.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8–10 ] Commonly used conductive polymers are usually based on a conjugated backbone structure, like in polyacetylene, polypyrrole, polyaniline, or polythiophene. [ 11 ] With different techniques of doping, [ 12–14 ] side chain variations, [ 14 ] or backbone modifications [ 15 ] the thermoelectric performance can be positively influenced.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we selected the indacenodithiophene (IDT) building block as the OTE material since the IDT skeleton has two thiophene rings attached with a central benzene ring that provide strong intermolecular interactions with ordered packing [ 26 , 27 , 28 ], which is beneficial for improving the electrical conductivity of OTE materials. IDT-based polymers have been widely used in organic field effect transistor (OFET) and solar cell applications [ 29 , 30 , 31 ]; however, although research on its TE properties has also been reported [ 32 , 33 ], the TE performance is still very low, and the detailed structure–property relationships are not comprehensive. In addition, we have recently reported IDT-based composite thermoelectric materials and found that the composites showed good performance with power factor of 161.34 mW/m −1 K 2 [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] due to their low toxicity, low thermal conductivity and mechanical flexibility. Recent results have shown that CPs are among the most promising materials for application in flexible thermoelectric generators [13][14][15][16][17]. For example, poly(3,4-ethylenedioxy-thiophene) (PEDOT) with a high thermoelectric figure of merit (ZT) of 0.45 has been reported [18], which stimulated the investigation of CPs to be used for thermoelectric generators.…”
Section: Introductionmentioning
confidence: 99%
“…Organic materials generally possess large Seebeck coefficients (S) and low thermal conductivity [13][14][15][16][17][18][19], therefore, the main challenge of achieving high-performance OTEs is how to improve the electrical conductivity of CPs without sacrificing their large Seebeck coefficients and low thermal conductivity [20,21]. Many strategies have been attempted to improve the conductivities of CPs (such as structural manipulations [22], strengthening the ordering of polymer packing [23], efficient doping [24], and forming composites with highly conductive inorganic materials [25], etc.…”
Section: Introductionmentioning
confidence: 99%